Menggali Potensi Energi Baru Terbarukan dari Air Asam Tambang di Danau Bekas Penambangan Batubara - Nurkhamim (Retii, 2021)
Coal mining activities can produce acid mine drainage which is concentrated in ex-mining lakes. In this study, acid mine water was tested from coal mining lakes into new renewable energy in the form of electrical energy. This research was conducted using the Galvanic Cell principle, by varying the copper (Cu), zinc (Zn) and carbon (C) electrodes into 9 pairs of electrodes by combining the C-Zn, Cu-C and Cu-Zn electrode pairs. In the combination of electrodes, testing was carried out at 3 locations of ex-mining lakes with different pH (Pit 1 = 5.1 , Pit 2 = 5.0, Pit 3 = 3.3) producing electrical energy for Pit 1 Cu-Zn = 11 ,5 ml Volts, C-Zn= 29.6 ml Volts, C-Cu = 45.9 ml Volts, Pit 2 Cu-Zn = 17.0 ml Volts, C-Zn= 31.1 ml volts, C-Cu = 48.6 ml Volts and Pit 3 Cu-Zn = 23.3 ml Volts, C-Zn = 47.4 ml Volts, C-Cu = 59.0 ml Volts. Overall, this study succeeded in finding 3 pairs of combinations of Voltaic Cells as new electrodes for producing new renewable energy in the form of potential electrical energy from acid water in the former mining lake. Theoretically, the ability to generate electrical energy is also positively correlated with the ability of the electrodes to store electrical energy as the wet battery principle. Keywords: acid mine drainage, Voltaic cell, electrode